My Family Stands Behind Me: Moderated Mediation Model of Family Support and Work Engagement - Humaira Erum; Ghulam Abid; Aizza Anwar; Muhammad Fazal Ijaz; Daisy Mui Hung Kee (MDPI AG, 2021)
Family motivation as a mediating mechanism is a novel and under-researched area in the field of positive organizational scholarship. Drawing on Social Exchange Theory (SET), this study empirically validates family motivation as a mediator between family support and work engagement. The process by Hayes (2013) was used to analyze time-lagged data collected from 356 employees of the education sector. Results confirm the mediating role of family motivation in the relationship between family support and work engagement and the moderating role of calling in the relationship between family support and family motivation. This study adds to the literature of family-work enrichment accounts by validating family support as a novel antecedent for family motivation and positive attitudes. The implications of the study are discussed.